Use of Case Studies in Montessori Leadership Preparation Programs - Damore, Sharon; Barbara Rieckhoff, Barbara (Journal of Montessori Research, 2025)
This paper examines the impact and relevance of the use of case studies as a teaching and learning tool in Montessori leadership programs. Frequently used as learning tools in educational leadership preparation programs, selected case studies were limited to those in Montessori leadership and language. Surveys and interviews with graduate students and program faculty were conducted to understand the relevance of case studies in coursework and to provide implications for further refinement of their use. Results suggest certain elements of case studies can enhance learning theory and serve as springboards to practice. Maria Montessori advocated for reflective practice; therefore, we are extrapolating that case studies may be a powerful and effective connection of scholarly study of theory to classroom practice. However, these benefits may not be well-clarified or highly valued in Montessori leadership coursework. With use of case studies in Montessori leadership coursework, an opportunity exists for faculty to reflect on strategies for using case studies and best practices. Content specific to Montessori settings may further support the usefulness and effectiveness of case studies and their impacts on student learning in Montessori leadership programs.